2013
DOI: 10.1111/cpr.12075
|View full text |Cite
|
Sign up to set email alerts
|

Roles of brain and muscle ARNT‐like 1 and Wnt antagonist Dkk1 during osteogenesis of bone marrow stromal cells

Abstract: These findings demonstrated that Bmal1 and Wnt signalling may have a synergistic effect at a particular stage of osteogenesis. Inhibition of Wnt signalling did not greatly affect ageing of MSCs through early passages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…Disruption of the Period genes results in a high bone mass due increased osteoblast proliferation in a systemic manner acting through the molecular clock in osteoblasts, whereas disruption of Bmal1 results in a low bone mass in a call autonomous manner resulting from a depletion of osteoprogenitors and their reduced ability to differentiate into osteoblasts and deposit bone matrix. This model is supported by recent observations that the reduced capacity of marrow stromal cells from aged mice to proliferate correlates with decreased mRNA and protein levels of BMAL1, while BMAL1 deficiency results in an increase in the number of senescent cells in different tissues, including bone marrow stromal cells (Chen et al, 2012; Lin et al, 2013; Khapre et al, 2011; He et al, 2013). Further experiments using conditional, tissue specific knock outs are needed to dissect systemic and cell autonomous mechanisms of the circadian clock and BMAL1 dependent control of bone formation.…”
Section: 0 Discussionsupporting
confidence: 65%
“…Disruption of the Period genes results in a high bone mass due increased osteoblast proliferation in a systemic manner acting through the molecular clock in osteoblasts, whereas disruption of Bmal1 results in a low bone mass in a call autonomous manner resulting from a depletion of osteoprogenitors and their reduced ability to differentiate into osteoblasts and deposit bone matrix. This model is supported by recent observations that the reduced capacity of marrow stromal cells from aged mice to proliferate correlates with decreased mRNA and protein levels of BMAL1, while BMAL1 deficiency results in an increase in the number of senescent cells in different tissues, including bone marrow stromal cells (Chen et al, 2012; Lin et al, 2013; Khapre et al, 2011; He et al, 2013). Further experiments using conditional, tissue specific knock outs are needed to dissect systemic and cell autonomous mechanisms of the circadian clock and BMAL1 dependent control of bone formation.…”
Section: 0 Discussionsupporting
confidence: 65%
“…Thus, investigation of the disordered mechanism of osteogenic differentiation in BMScs and development of effective methods of prevention and early therapy are crucial. a number of previous studies have reported that osteogenic differentiation-related genes are expressed periodically (5,6). Brain and muscle arnT-like 1 (BMal1) is the most important component of the molecular biological clock, expression of which has been found to have 24-h periodicity in bone.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of Bmal1 could promote bone mesenchymal stem cell (BMSC) proliferation, and this process was relatively independent of Bmal1 regulation of circadian rhythm, testifying that Bmal1 could inhibit cell aging [12]. Furthermore, the expression of b-catenin, the key factor of Wnt/b-catenin signaling, increased when Bmal1 was overexpressed [13], and another study showed that b-catenin expression decreased with aging [14]. As the main signaling pathway in development, Wnt/b-catenin signaling may play vital roles in the aging process [15,16].…”
Section: Introductionmentioning
confidence: 99%